Hubungan Tingkat Pengetahuan tentang Dismenore dengan Perilaku Penanganan Dismenore pada Remaja Putri di Desa Karanggintung - Dewi Ambarwati; Hestiyah Hestiyah (Universitas Ngudi Waluyo, 2022)
The incidence of dysmenorrhea in the world is very large, on average more than 50% of women in the world experience dysmenorrhea. The results of research in America for the incidence of dysmenorrhea about 60%, Sweden 72% and in Indonesia 55%. The purpose of the study was to determine the relationship between the level of knowledge about dysmenorrhea and the behavior of handling dysmenorrhea in adolescent girls in the village of Karanggintung. The research method is descriptive survey research with a quantitative approach with cross sectional design. The sample with total sampling technique is that all young women who experience dysmenorrhea in Karanggintung Village are 35 people. The research instrument is a questionnaire to measure the level of knowledge and behavior in handling dysmenorrhea. The results of the study are the age of the majority of young women in middle teens (14-16 years) totaling 18 respondents (51.4%), the majority of education in low education amounting to 22 respondents (62.8%), the majority of knowledge about dysmenorrhea in sufficient knowledge amounting to 25 respondents (71.4%), the majority of the behavior in handling dysmenorrhea was 33 respondents (94.3%). Good knowledge about dysmenorrhea with poor behavior in handling dysmenorrhea amounted to 1 respondent (100%). There is a relationship between the level of knowledge about dysmenorrhea with the behavior of handling dysmenorrhea in adolescent girls in Karanggintung Village.